A remarkable new Iguanura (Arecaceae, Arecoideae, Areceae) from northern Myanmar - Henderson, Andrew; Aung, Mu Mu; Armstrong, Kate (Phytotaxa, 2020)
A new species of Iguanura from northern Myanmar is described and illustrated.